The Necessity of English for Specific Purposes at the Law Universities of the Republic of Kazakhstan - Yelena Vyacheslavovna Yemelyanova; Flyura Rifkhatovna Avazbakiyeva; Anar Bauyrzhanovna Ibrayeva; Aizhan Zharkynovna Aikenova (International Review of Management and Marketing, 2016)
English for specific purposes (ESP) constitutes the minority of courses in the English language disciplines at Kazakhstani Universities. Among possible explanations are that it is costly, time consuming and an intellectually challenging specialization process on the part of the teacher and a more complex and challenging subject for the student, though students don’t lack the basic language skills necessary to benefit fully from such specific purpose classes. This article focuses on the teaching of Legal English to students of International law specialty in the Republic of Kazakhstan. It touches upon the history of language for specific purposes, material used in the Legal English classes, and the students themselves. It concludes with the case study investigating trends in Legal English classroom among students of International Legal English at Kazakh Humanities and Law University. This article also deals with the levels of skills necessary for students attending International Legal English classes and the results that students achieve. It concludes that although the need for International legal English in Kazakhstan is not yet realized, it needs to be, if the country wants to cooperate successfully in the world stage and contribute to the international and local legal environment.